Cultural Practices For Postpartum And Breastfeeding Care In The Ammatoa Indigenous Community - Sri Ningsih; Sulastri Sulastri; Sumarni Sumarni; Erniawati Erniawati; Arfiani Arfiani; Husnul Khatimah (Jurnal Mamangan, 2023)
The Ammatoa Community in Kajang is an indigenous group that continues to uphold their customs and culture in the present time. The culture and practices they follow are thought to have the capacity to mitigate the occurrence of stunting in children. In the context of postpartum and breastfeeding care, a range of activities are implemented to guarantee the highest level of nutrition for both mothers and infants. Hence, the cultural aspect of this group also serves as a contributing component in endeavors to reduce the prevalence of stunting. The purpose of this study is to delve into the culture of care for postpartum and breastfeeding mothers in the Ammatoa indigenous community, with the aim of supporting the prevention of stunting. This study employs a qualitative methodology, utilizing in-depth interviews as the means of data gathering. The informants were selected using the snowball sampling approach in Benteng Hamlet, Tanah Toa Village, Community District, Bulukumba Regency. The study identified two interventions for women experiencing postpartum and breastfeeding. Initially, hemorrhage prophylaxis was implemented by administering rappo leaves to postpartum mother on the day following delivery, subsequently followed by cleansing the perineum with water. A heated concoction blended with desiccated banana leaves for the purpose of treating perineal lesions. Moreover, the practice of applying lambere susu leaves on postpartum breasts serves to enhance and expedite the breastfeeding mothers’ lactation process. The findings indicate that the cultural practices of caring for postpartum women and promoting breastfeeding within the Ammatoa Community indigenous community have a positive impact on the health of both mothers and infants, hence contributing to the prevention of stunting.